Evidence on the Insurance Effect of Redistributive Taxation - Grant, Charles; Koulovatianos, Christos; Michaelides, Alexander; Padula, Mario (The Review of Economics and Statistics, 2010)
If households face uninsurable idiosyncratic earnings risk, theory predicts that redistributive tax and transfer systems have both an insurance and a distortionary effect. Exploiting the substantial variation of tax and transfer systems across U.S. states and over time, we investigate the necessary traces of these two effects in the data: that state-level measures of redistributive taxation should correlate negatively with the standard deviation and the mean of the within-state consumption distribution. We find that the first correlation is robust, supporting strongly the presence of an insurance effect. The distortionary effect can also be detected in the data, but it is less precisely estimated.